2015
DOI: 10.1130/b31130.1
|View full text |Cite
|
Sign up to set email alerts
|

Along-strike variation in crustal shortening and kinematic evolution of the base of a retroarc fold-and-thrust belt: Magallanes, Chile 53°S-54°S

Abstract: The Late Cretaceous closure of the Late Jurassic-Early Cretaceous Rocas Verdes basin resulted in the development of the Patagonian fold-and-thrust belt and Magallanes foreland basin between 50°S and 54.5°S. New geologic maps, structural data, and two retrodeformed, line-balanced cross sections from the Magallanes region of Chile (53°S-54°S) constrain the kinematic evolution and along-strike correlations of deformation that occurred at the base of the fold-and-thrust belt near the brittle-ductile transition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 92 publications
3
45
1
Order By: Relevance
“…This kind of response of preexisting and new normal faults upon flexural loading in foreland basins has been documented in many other similar geological settings [ Bradley and Kidd , ; Agarwal et al ., ; Londoño and Lorenzo , ; von Hartmann et al ., ], including the South Malvinas basin which is laterally linked to the Austral‐Magallanes basin [ Platt and Philip , ; Bry et al ., ]. It is also interesting to point out, regarding interpretations of inversion of normal faults published elsewhere [ Betka et al ., ], that only one possible inverted normal fault, with a displacement of a few hundred meters, was recognized within our data set (section C‐C′), suggesting no major influence of inversion tectonics during shortening in the Fuegian thrust‐fold belt.…”
Section: Geometric Analysismentioning
confidence: 73%
“…This kind of response of preexisting and new normal faults upon flexural loading in foreland basins has been documented in many other similar geological settings [ Bradley and Kidd , ; Agarwal et al ., ; Londoño and Lorenzo , ; von Hartmann et al ., ], including the South Malvinas basin which is laterally linked to the Austral‐Magallanes basin [ Platt and Philip , ; Bry et al ., ]. It is also interesting to point out, regarding interpretations of inversion of normal faults published elsewhere [ Betka et al ., ], that only one possible inverted normal fault, with a displacement of a few hundred meters, was recognized within our data set (section C‐C′), suggesting no major influence of inversion tectonics during shortening in the Fuegian thrust‐fold belt.…”
Section: Geometric Analysismentioning
confidence: 73%
“…Closure of the Patagonian sector of the Rocas Verdes basin began in Early Cretaceous time (Fildani & Hessler, ; Malkowski et al ., ; Betka et al ., ) as subduction began along the western margin of South America. This caused obduction of the Sarmiento ophiolite complex and growth of the Andean volcanic arc and fold‐thrust belt (Wilson, ; Fildani & Hessler, ; Fildani et al ., ; Calderón et al ., ; Torres‐Carbonell & Dimieri, ).…”
Section: Geologic Settingmentioning
confidence: 99%
“…Shoaling during the transition between the Tres Pasos-Fuentes to Dorotea-Rocallosa formations within a normal regressive context can be ascribed to increases in sedimentation rates that outpaced accommodation (by subsidence), the aftermath of accentuated erosion in the hinterland. The results of structural studies suggest an orogen-wide basement-involved faulting event (thick-skinned) manifested by crustal basement shortening and internal deformation (e.g., Fosdick et al, 2011;Betka et al, 2015). Altogether, the fold-thrust-belt evolution and sedimentary records in the basin suggest a phase of mainly internal shortening and thickening of the wedge, with limited forelandward advance of the deformation front (Fig.…”
Section: Journal Pre-proofmentioning
confidence: 94%
“…In the Ultima Esperanza Province, it is inferred by the Tenerife thrusting (with a basal décollement on the argillaceous Zapata Formation) between 74-27 Ma (Fosdick et al, 2011), which continued exhuming the Tobífera Formation and incorporated Upper Cretaceous foredeep deposits into the fold-thrust belt. In the Magallanes Province, Betka et al (2015) suggested a phase of out-of-sequence thrusting and basement-involved reverse faulting beginning in the Maastrichtian and extending to the Paleogene. The deformation and cooling ages of ophiolitic blocks in the hinterland around 74-72 Ma (Rapalini et al, 2008) together with progradation and depositional system shoaling (Tres Pasos and Dorotea formations) (Covault et al, 2009;Romans et al, 2009;Schwartz and Graham, 2015;Schwartz et al, 2017;Gutiérrez et al, 2017) may also reflect deformation in the fold-thrust belt.…”
Section: Tectonic Events In the Fold-thrust Beltmentioning
confidence: 99%
See 1 more Smart Citation